2018
DOI: 10.30998/sap.v2i3.2450
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Web Based Learning terhadap Hasil Belajar Ditinjau dari Self-Directed Learning

Abstract: AbstrakTujuan penelitian ini adalah untuk mengetahui pengaruh dan interaksi antara pembelajaran kimia dengan model web based learning menggunakan moodle dan blog terhadap hasil belajar kognitif siswa kelas X pada materi ikatan kimia ditinjau dari kemampuan self-directed learning (SDL) siswa yang berbeda. Penelitian ini menggunakan rancangan penelitian eksperimental semu yaitu posttest onlynonequivalent control group design. Pengambilan sampel menggunakan teknik cluster random sampling. Data penelitian adalah h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The case is also uniquely similar in the workplace as found by Lejeune et al (2021), where self-directed learning positively influences employees' job performance. In addition, a study conducted by Rahayu (2015) revealed that there was a relationship between the learning model and students' self-directed learning abilities on students' cognitive learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The case is also uniquely similar in the workplace as found by Lejeune et al (2021), where self-directed learning positively influences employees' job performance. In addition, a study conducted by Rahayu (2015) revealed that there was a relationship between the learning model and students' self-directed learning abilities on students' cognitive learning outcomes.…”
Section: Introductionmentioning
confidence: 99%